Enhancing the efficacy of platinum-based chemotherapeutics by targeting BRCA1 - Garbuio, Kyla D (University of Ottawa (Canada), 2010)
Decreased expression of Breast Cancer 1 protein BRCA1 in breast and epithelial ovarian cancer patients has been correlated with increased overall survival. The improved outcome of patients with BRCA1-deficient tumours has been linked to their impaired ability to repair DNA damage induced by chemotherapy, specifically platinum agents. Targeting the DNA repair protein BRCA1 using novel therapeutic approaches has the potential to enhance platinum chemosensitivity in breast and ovarian cancer. Human ovarian and breast cancer cell lines were treated for 24 or 48 hours with three standard chemotherapeutics alone or in combination with three small molecule inhibitors that target DNA repair activity. Treatment with a histone deacetylase inhibitor sensitized breast and ovarian cancer cell lines to platinum agents. The HDACi significantly decreased BRCA1 RNA and protein expression. The HDACi shows promise as a therapeutic agent in combination with platinum therapy for breast and ovarian cancer due to its ability to down-regulate BRCA1.
Keywords: Chemistry, Biochemistry.